Characterization of TiO2 Loaded on Activated Carbon Fibers and Its Photocatalytic Reactivity - 贾冰玉 段利艳 马传利 王春明 (Chinese journal of chemistry, 2007)
In this paper, TiO2 loaded on activated carbon fibers （ACF） was prepared by a coating treatment, followed by calcination at different temperatures in air atmosphere. The photocatalyst developed was characterized by SEM, XRD, XPS and UV-Vis adsorption spectroscopy. It was observed from SEM images that TiO2 loaded on ACF was in the form of small clusters with nanometer size. As confirmed by XRD and XPS determinations, the crystalline pattern of immobilized TiO2 was still anatase-form after calcination, and the micrographic structure and surface properties of ACF have not been damaged by the deposition process and calcination at different temperatures. Photocatalytic degradation of methylene blue （MB） in aqueous .solution was investigated using TiOE/ACF as photocatalyst. The comparison of photolysis, absorption and photocatalysis was carded out. The results indicated that the photocatalysis process of combined photocatalyst showed much higher degradation rate than that of photolysis and absorption processes. In addition, the possibility of cyclic usage of the photocatalyst was also confirmed.